Early evaluation of the transition from an analog to an electronic surgical logbook system in Sierra Leone - Sophia Sung (BMC, 2021)
Abstract Background Surgical logbooks are a commonly used tool for quality assurance of surgical training. Electronic logbooks are increasingly applied in low-resource settings, but there is limited research on their quality. The aim of this study is to evaluate the quality of an app-based surgical e-logbook system shortly after its implementation in a low-income country and to identify potential areas of improvement for the system. Methods Entries in the e-logbook system were cross-checked with hospital records and categorized as matched or overreported. Moreover, the hospital records were checked for underreported procedures. Additionally, semi-structured interviews were conducted with users of the e-logbook system. Results A total of 278 e-logbook database entries and 379 procedures in the hospital records from 14 users were analyzed. Matches were found in the hospital records for 67.3% of the database entries. Moreover, 32.7% of the database entries were overreported and 50.7% of the procedures in the hospital records were underreported. A previous study of an analog surgical logbook system in the same setting estimated that 73.1% of the entries were matches or close matches. Interviews with 12 e-logbook users found overall satisfaction but also identified potential areas of improvement, including the need for more training in the use of the system, modifications to improve user-friendliness, and better access to the necessary technology. Conclusions A reliable documentation system is necessary to evaluate the quality of health workforce training. The early evaluation of a surgical e-logbook system in a low-income country showed that the collected data should be approached with caution. The quantitative analysis suggests that the e-logbook system needs to be improved in terms of accuracy. In interviews, users reported that digitalization of the logbook system was a much-needed innovation but also identified important areas of improvement. Recognition of these aspects at an early stage facilitates guidance and adjustment of further implementation and might improve the accuracy of the system.